Electronic transitions in α, θ and γ polymorphs of ultraporous monolithic alumina. Issue 11 (13th August 2013) - Museur, L.; Bouslama, M.; Amamra, M.; Kanaev, A.
Abstract Spectroscopy of α, θ, and γ phases of high‐purity ultraporous alumina has been studied at cryogenic temperatures of 7 K in the near‐IR–VUV range of spectra with synchrotron radiation excitation. The UV photoluminescence (PL) spectra are dominated by optical transitions of self‐trapped excitons, while the PL excitation spectra are assigned to free excitons and interband transitions. The analysis of PL excitation spectra indicates a tendency to fundamental bandgap narrowing in order of 9.36 eV (α) to 7.60 eV (θ) and 6.85 eV (γ). Structural defects related to oxygen vacancies are responsible for the visible F+/F transitions decrease in order γ > θ > α. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)